Помогитеее !! (подробно)

0 голосов
32 просмотров

Помогитеее !! (подробно)


image

Алгебра | 32 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

156
2
f(x)=x-1
h→0
f(x+h)-f(x)=lim[(x+h)-1-(x-1)]/h=lim(x+h-1-x+1)/h=limh/h=1
4
f(x)=x²+2
h→0
lim[(x+h)²+2-(x²+2)]/h=lim(x²+2xh+h²+2-x²-2)/h=lim(2xh+h²)/h=
=lim(2x+h)=2x+0=2x
6
f(x)=2x³+x
h→0
lim[(x+h)³=(x+h)-(2x³+x)]/h=lim(2x³+6x²h+6xh²+h³-2x²-x)/h=
=lim(6x²h+6xh²+h³+h)/h=lim(6x²+6xh+h²+1)=6x²+6x*0+0+1=6x²+1
158
2
f(x)=-4x
f`(x)=-4
4
f(x)=-7x-8
f`(x)=-7

(750k баллов)